2006
DOI: 10.2118/92991-pa
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Reservoir Model Updating Using Ensemble Kalman Filter With Confirming Option

Abstract: Summary The ensemble Kalman Filter technique (EnKF) has been reported to be very efficient for real-time updating of reservoir models to match the most current production data. Using EnKF, an ensemble of reservoir models assimilating the most current observations of production data is always available. Thus, the estimations of reservoir model parameters, and their associated uncertainty, as well as the forecasts are always up-to-date. In this paper, we apply the EnKF for con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(66 citation statements)
references
References 19 publications
0
66
0
Order By: Relevance
“…The permeabilities updated after an analysis step were used again as input to recalculate the last time step and to obtain the corrected pressure solution. Wen and Chen [2006] found that their approach outperformed noniterative EnKF. Moradkhani et al [2005] handled the joint estimation of states and parameters with a dual approach.…”
Section: Joint Estimation Of States and Parametersmentioning
confidence: 98%
See 2 more Smart Citations
“…The permeabilities updated after an analysis step were used again as input to recalculate the last time step and to obtain the corrected pressure solution. Wen and Chen [2006] found that their approach outperformed noniterative EnKF. Moradkhani et al [2005] handled the joint estimation of states and parameters with a dual approach.…”
Section: Joint Estimation Of States and Parametersmentioning
confidence: 98%
“…Wen and Chen [2006] proposed a rerun option to solve these problems. The permeabilities updated after an analysis step were used again as input to recalculate the last time step and to obtain the corrected pressure solution.…”
Section: Joint Estimation Of States and Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Oliver (2004, 2005a, b) investigated a highly nonlinear problem of facies estimation using the EnKF method. When using the EnKF method, Lorentzen et al (2005) discussed the choice of initial ensemble members, while Wen and Chen (2006) focused on the effect of ensemble size. Reynolds (2012, 2013) incorporated automatic history matching in an integrated geomodeling workflow using the ensemble smoother method.…”
Section: Gradient-free Algorithmsmentioning
confidence: 99%
“…Several studies argued that the joint EnKF may suffer from important inconsistencies between the estimated state and parameters that could degrade the filter performance, especially with large-dimensional and strongly nonlinear systems (e.g., Moradkhani et al, 2005b;Chen and Zhang, 2006;Wen and Chen, 2007). One classical approach that has been proposed to tackle this issue is the so-called dual filter, which separately updates the state and parameters using two interactive EnKFs, one acting on the state and the other on the parameters (Moradkhani et al, 2005b).…”
Section: Introductionmentioning
confidence: 99%